2003
DOI: 10.1259/bjr/82051842
|View full text |Cite
|
Sign up to set email alerts
|

Effective techniques for reduction of radiation dosage to patients undergoing invasive cardiac procedures

Abstract: The goal of this study was to improve radiation dose reduction techniques in invasive cardiology and after patients' radiation data had approached minimal levels, to evaluate predictors of their radiation exposure resulting from invasive cardiac procedures. Over the course of 1 year (and 1996 procedures) we minimized cinegraphic frames and runs, as well as fluoroscopy time, and trained ourselves to achieve effective fluoroscopy-saving positioning of blinds and filters toward the regions of interest. We were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 20 publications
6
83
1
9
Order By: Relevance
“…These means involve the use of protective shielding, maintaining the distance from the x-ray source and being mindful of the positioning of basic equipment, the limitation of the time of exposure, and optimization of the x-ray emission parameters (table 1) [4,8,25]. Data on x-ray optimization parameters (FR, resolution, exposure dose expressed as air kerma and DAP) are by default provided in all modern angiography equipment for radiation exposure monitoring in real time.…”
Section: Discussionmentioning
confidence: 99%
“…These means involve the use of protective shielding, maintaining the distance from the x-ray source and being mindful of the positioning of basic equipment, the limitation of the time of exposure, and optimization of the x-ray emission parameters (table 1) [4,8,25]. Data on x-ray optimization parameters (FR, resolution, exposure dose expressed as air kerma and DAP) are by default provided in all modern angiography equipment for radiation exposure monitoring in real time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, substantial dose reduction (both E and scatter) can be achieved by making active use of collimation, and ensuring that the fluoroscopy and fluorography frame rates (as well as the detector entrance dose rates in these modes) are as low as necessary for the clinical task [19,20]. Furthermore, scatter dose to the cardiologist can be significantly reduced through the use of appropriate personal protective equipment, as well as table-, floor-and ceiling-mounted operator shielding.…”
Section: Radiation Use Optimisation In Cardiac Angiographymentioning
confidence: 99%
“…minimising the X-ray dose to the patient while preserving the quality of treatment), the use of low fluoroscopy pulse rate, image intensifier field size and collimation are recommended [1,12,13]. However, the studies that concluded that there was an impact on dose of some technical parameters had mostly used descriptive or univariate analyses and/or were carried out on a phantom [2,4,14,15]. Few studies have used multivariate methods to analyse the dose variation on patients' skin [13,16].…”
mentioning
confidence: 99%